2021
DOI: 10.1055/s-0041-1736179
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorder: An Overlooked Manifestation of Glucose Transporter Type-1 Deficiency Syndrome

Abstract: Glucose transporter type-1 deficiency syndrome (Glut1 DS) is a rare disorder with various manifestations. Early diagnosis is crucial because treatment with the ketogenic diet can lead to clinical improvement. Here, we report the cases of two siblings with Glut1 DS and one of them presented with sleep disorder which is a rare and atypical manifestation of Glut1 DS. Patient 1 was a 3.5-year-old boy who presented with paroxysmal loss of tone and weakness of the whole body with unresponsiveness after waking up. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A total of 20 articles published between 2001 and 2022 were included: nine prospective studies divided between eight single‐centre (Ebus et al, 2014; Guzel et al, 2019; Hallböök, Köhler, et al, 2007; Hallböök, Lundgren, & Rosén, 2007; Li et al, 2023; Merlino et al, 2023; Wu et al, 2018; Zhu et al, 2016) and one multi‐centre (Miranda et al, 2011), eight retrospective studies, divided between three single‐centre (Nordli et al, 2001; Peng et al, 2019; Reyes et al, 2015) and five multi‐centre, one of which longitudinal study (Sofou et al, 2017) and four cross‐sectional (Alqahtani & Mahmoud, 2016; Caraballo et al, 2011; Frye et al, 2011; Ünalp et al, 2021), two case reports (Anurat et al, 2022; Melikishvili et al, 2022), one two‐arm open RCT (Kverneland et al, 2018). Of these 20 articles, only one study is related to migraine while 18 studies have epilepsy as a starting diagnosis and one study is related to autism spectrum disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 articles published between 2001 and 2022 were included: nine prospective studies divided between eight single‐centre (Ebus et al, 2014; Guzel et al, 2019; Hallböök, Köhler, et al, 2007; Hallböök, Lundgren, & Rosén, 2007; Li et al, 2023; Merlino et al, 2023; Wu et al, 2018; Zhu et al, 2016) and one multi‐centre (Miranda et al, 2011), eight retrospective studies, divided between three single‐centre (Nordli et al, 2001; Peng et al, 2019; Reyes et al, 2015) and five multi‐centre, one of which longitudinal study (Sofou et al, 2017) and four cross‐sectional (Alqahtani & Mahmoud, 2016; Caraballo et al, 2011; Frye et al, 2011; Ünalp et al, 2021), two case reports (Anurat et al, 2022; Melikishvili et al, 2022), one two‐arm open RCT (Kverneland et al, 2018). Of these 20 articles, only one study is related to migraine while 18 studies have epilepsy as a starting diagnosis and one study is related to autism spectrum disorder.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies included, sleep improvement was almost never preceded by a systematic screening for sleep disorder at baseline, before the initiation of ketogenic dietary therapies. One study reported an improvement of sleep disorder after ketogenic dietary therapy in the case description of a patient with GLUT1 deficiency syndrome, who presented with sleep‐onset insomnia and restless sleep during the night, together with excessive daytime sleepiness (Anurat et al, 2022). The polysomnography at baseline and Multiple Sleep Latency Test findings showed a pathological periodic limb movement index and daytime sleepiness.…”
Section: Resultsmentioning
confidence: 99%
“…Our study suggested that SLC2A1 might be an upstream regulator of SHISA8. SLC2A1 is a glucose transporter primarily located in the blood-brain barrier [40] , whose nonsense or missense mutations induced daytime sleepiness and insomnia [41,42] . Although a recent study in a small cohort suggested increased glutamine level in cerebrospinal uid of SLC2A1 de ciency patients [43] , whether SLC2A1 affects sleep-wake activity through the glutaminergic system or SHISA8 remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency of insomnia has been observed in Sydenham's chorea. Additionally, sudden sleep episodes, insomnia, EDS, and paroxysmal loss of tone or weakness upon awakening have been reported in glucose transporter type 1 deficiency syndrome (GLUT1-DS), a rare metabolic encephalopathy linked to paroxysmal exerciseinduced dyskinesias [49,50].…”
Section: Other Choreiform Disordersmentioning
confidence: 99%